Navigating the COVID-19 storm: Impact of the pandemic on the Philippine economy and macro responses of government - Margarita Debuque-Gonzales (Philippine Institute for Development Studies (PIDS), 2021)
The Philippines entered its deepest recession in post-war history in 2020, with output declining by 9.6 percent. Coming up with a strategy on how to best manage the economy and deal with the fallout of the public health shock, especially on the weaker segments of society, became the biggest challenge of the country's economic policymakers. This chapter/paper looks more closely at that episode, dissecting the macroeconomic impact of the coronavirus, viewing it up close through its impact on households and firms, and then chronicling and reviewing the macroeconomic policy responses of government. It ends by summarizing the lessons to carry and the options on the path forward - for the near future - as the country continues to struggle with the pandemic, and for when it enters a more normalized (post-pandemic) world.
Keywords: 330; COVID-19 pandemic; public health shock; macroeconomic impact; macroeconomic policy response; Philippine economy